2018
DOI: 10.1074/jbc.ra118.001977
|View full text |Cite
|
Sign up to set email alerts
|

The unassembled flavoprotein subunits of human and bacterial complex II have impaired catalytic activity and generate only minor amounts of ROS

Abstract: Complex II (SdhABCD) is a membrane-bound component of mitochondrial and bacterial electron transport chains, as well as of the TCA cycle. In this capacity, it catalyzes the reversible oxidation of succinate. SdhABCD contains the SDHA protein harboring a covalently bound FAD redox center and the iron-sulfur protein SDHB, containing three distinct iron-sulfur centers. When assembly of this complex is compromised, the flavoprotein SDHA may accumulate in the mitochondrial matrix or bacterial cytoplasm. Whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 74 publications
(111 reference statements)
0
27
0
Order By: Relevance
“…An interdomain rotation of the assembly intermediates appears to cause the altered alignment of these active site residues (22,23). This prompted the structural prediction that the active site can no longer catalyze succinate-fumarate interconversion in this pose, which was consistent with kinetic analysis of the assembly intermediate, which lacks detectable succinate-fumarate interconversion activity (24). Despite the similarities in these two structures, the magnitude and the direction of this interdomain rotation was substantially different, creating controversy as to which of these accurately captured an onpathway pose in the assembly process.…”
Section: Significancementioning
confidence: 72%
See 1 more Smart Citation
“…An interdomain rotation of the assembly intermediates appears to cause the altered alignment of these active site residues (22,23). This prompted the structural prediction that the active site can no longer catalyze succinate-fumarate interconversion in this pose, which was consistent with kinetic analysis of the assembly intermediate, which lacks detectable succinate-fumarate interconversion activity (24). Despite the similarities in these two structures, the magnitude and the direction of this interdomain rotation was substantially different, creating controversy as to which of these accurately captured an onpathway pose in the assembly process.…”
Section: Significancementioning
confidence: 72%
“…In vitro SDHAF2-dependent flavinylation of SDHA in the presence of a dicarboxylate was previously shown by Zafreen et al (25), although progress was hampered by both the instability of SDHA and the poor expression levels of SDHA. Toward the overall goal of in vitro flavinylation, prior work from us and others improved expression levels of SDHA using codon optimization (24), but the expression of functional and assembled human complex II continues to elude the field. This suggests that, to date, all components needed for human SDHA maturation and flavinylation have not been correctly defined.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that about 90% of the ROS formed in bacteria under oxic growth conditions are generated by the electronic transport chain (ETC) (Scialò et al ., ; Maklashina et al ., ), the specific rates of respiration and O 2 · − formation were assessed in the strains under study (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, Maklashina et al showed that free E. coli SDHA flavoproteins have only minor catalytic activity and generate little or no ROS. Their results suggest that the iron-sulfur protein SDHB in CII is necessary for robust catalytic activity and ROS generation by incomplete CII [58]. This could explain how CII could produce ROS to amplify the apoptotic response.…”
Section: The Paradox Of Ros Production From CIImentioning
confidence: 99%